Chinese Parent Intention to Vaccinate Children With Special Diseases Against COVID-19 - Wang, Xu; Yan, Wu; Lu, Lingling; Cao, Liming; Tian, Ye; Zhou, Kai (Frontiers in Public Health, 2021)
Background: Information on the intention of parents of children with special diseases to vaccinate their children against COVID-19 is scarce. Methods: In this survey, all participants(n=914) were enrolled from a tertiary children’s hospital between September 2020 and April 2021. A face-to-face questionnaire interview was conducted to collect the information of the special diseases of children and parental attitudes about COVID-19 vaccine. We compared the demographic and disease factors between the group of parents who were willing to vaccinate their children against COVID-19 and the group who were unwilling to vaccinate. Results: Among 941 children, 58.1% (n=547) were boys. Mean age was 1.4 (SD 1.9) years. If COVID-19 vaccine becomes available for child, 470 (49.9%) of parents willing to provide vaccination for their children. The less education levels of the father or mother, the more likely they were to vaccinate their children (P=0.003, P=0.007). However, more intentions to vaccinate was provide in parents of children with COVID-19 prevention and control education (P<0.001). Conclusion: Our findings provided evidence that some parents are willing to vaccinate their children with special diseases against COVID-19. Professional knowledge about COVID-19 prevention and control may contribute to increased parental intention.